Implementasi Metode Agile Scrumban Dalam Penjualan Jasa Pembuatan Aplikasi Pada PT. Labani - Gea, Lusiana Aliran Pinta Wati; Leni Marlina (Jurnal Mahajana Informasi, 2024)
PT. Labani faces challenges in improving the efficiency and flexibility of its application development service sales process. The traditional methods used so far have been inadequate in accommodating clients' changing needs quickly and efficiently. This research aims to address these issues by implementing the Agile Scrumban method, which combines the strengths of Scrum and Kanban. The study was conducted through a case study approach with qualitative methods, including direct observation, in-depth interviews with sales and development team members, and analysis of internal company documents. The implementation of Agile Scrumban began with intensive training for the team, followed by gradual application in sales and application development projects. The research results indicate that Agile Scrumban successfully improved inter-team coordination, reduced project lead time, and provided better visibility into sales and development progress. Issues such as team adjustment to the new method and synchronization between sales and development were addressed through ongoing training and enhanced communication. Thus, the implementation of the Agile Scrumban method at PT. Labani proved effective in resolving efficiency and flexibility issues and increasing customer satisfaction. Recommendations for the company include additional training and strengthening inter-departmental integration to ensure the smooth adoption of this method.